2018
DOI: 10.1016/j.nmd.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A zebrafish model for FHL1-opathy reveals loss-of-function effects of human FHL1 mutations

Abstract: Missense mutations in the four and a half LIM domain 1 (FHL1) gene were found to cause X-linked inherited myopathies of both skeletal and heart muscles. However, the mechanisms by which FHL1 mutations impact on FHL1 function and lead to alteration of muscle structure and function have not been deciphered yet. We generated here by Morpholino-modified antisense oligonucleotide-mediated gene knockdown fHL1-deficient zebrafish embryos. Similar to the human situation, fhl1a-morphants zebrafish displayed severe skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have reported defects in muscle fiber structure and mass due to the absence of FHL1. Keßler et al () found that FHL1 knockout caused skeletal muscle structural defects accompanied by muscle fiber disorders in zebrafish. Domenighetti et al () found that the deletion of FHL1 leads to age‐dependent skeletal muscle myopathies associated with myofibrillar and intermyofibrillar disorganization in mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported defects in muscle fiber structure and mass due to the absence of FHL1. Keßler et al () found that FHL1 knockout caused skeletal muscle structural defects accompanied by muscle fiber disorders in zebrafish. Domenighetti et al () found that the deletion of FHL1 leads to age‐dependent skeletal muscle myopathies associated with myofibrillar and intermyofibrillar disorganization in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The FHL1 gene encodes a 280‐amino‐acid protein containing a zinc finger and four LIM domains that mediate protein–protein interactions in the cytoplasm and nucleus (Dawid, Breen, & Toyama, ). FHL1 is predominantly expressed in skeletal and cardiac muscles where it regulates growth and development through its action as a scaffolding protein during sarcomere assembly (Keßler et al, ). FHL1 mutations cause a series of muscular disorders, including postural muscle atrophy (Keßler et al, ), reduced body myopathy (Selcen, Bromberg, Chin, & Engel, ), X‐linked dominant scapuloperoneal myopathy (Chen et al, ), rigid spine syndrome (Shalaby et al, ), hypertrophic cardiomyopathy (Friedrich et al, ), and Emery–Dreifuss muscular dystrophy (Knoblauch et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas in the beginnings of zebrafish research, developmental biology studies had priority [40,[56][57][58][59][60], more and more, the ability to model essential features of human cardiac disorders moved into the center of attraction [51,[61][62][63][64][65]. Since early development of zebrafish embryos does not require proper blood circulation, this model organism is amenable to a broad range of functional genomic approaches including forward genetics by e.g.…”
Section: Modeling Human Cardiovascular Disorders Using the Zebrafishmentioning
confidence: 99%
“…Based on zebrafish transparency during embryogenesis functional impact on zebrafish cardiovascular system after genome/gene editing can be easily evaluated via simple light microscopy. Using innovative functional genomic approaches several important key molecules regulating cardiac pump function and rhythm were identified leading to a more in-depth understanding of important human cardiac disorders such as cardiomyopathies, arrhythmias or heart failure [38,51,63,64,70] Large forward genetic screens led to the identification of numerous zebrafish mutants with heart defects resembling severe human cardiac pathologies such as cardiomyopathies, valvular defects, arrhythmias and heart failure [57]. Genetic analyses by positional cloning of these mutants identified known and novel genes and molecular pathways of cardiovascular disease and demonstrated the validity of the zebrafish to simulate and model human cardiovascular diseases as well as to dissect the molecular pathomechanisms of human CVD (selected zebrafish mutants see Table 2).…”
Section: Modeling Human Cardiovascular Disorders Using the Zebrafishmentioning
confidence: 99%